Forestry Building and water tower, University of Washington campus, Seattle, Washington, between 1909 and 1931 - Cobb, J. N. (1909)
PH Coll 778.22 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number Scanned from a photographic print at 100 dpi in JPEG format at compression rate 3 and resized to 768x600 ppi. 2018